Serving the empire in the Great War the Cypriot Mule Corps, imperial loyalty and silenced memory - Varnava, Andrekos 1979- (Studies in Imperialism, 2017)
This book contributes to the growing literature on the role of the British non-settler empire in the Great War by exploring the service of the Cypriot Mule Corps on the Salonica Front, and after the war in Constantinople